Rapid early-strength self-repairing sprayed concrete and construction method thereof
By adopting a synergistic mechanism between dual microcapsules and fast early strength system in sprayed concrete, the problems of low early strength, high cracking risk and low self-repair efficiency in deep foundation pit support are solved, and efficient self-repair and early strength improvement are achieved.
Patent Information
- Application Number
- CN202411749313.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
AI Technical Summary
The existing sprayed concrete has problems in the early stage of low strength, high cracking risk, and low self-repair efficiency in deep foundation pit support, and the traditional construction technology is complex and quality control is difficult.
The synergistic mechanism of dual microcapsules and fast early strength system is adopted to achieve synchronous improvement of concrete self-repair performance and early strength through complex interface regulation and precise design of functional components. Specifically, it includes introducing a composite microcapsule system and a fast and early strength system into the functional layer, and ensuring effective combination between each functional layer through layered jetting process and interface strengthening technology.
Breakthrough indicators such as 1d compressive strength ≥15MPa, crack repair rate ≥90%, and interface bonding strength ≥2.5MPa were achieved, providing a new technical route for improving the performance of jet concrete.
Smart Images

Figure CN119661127A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of shotcrete, and in particular relates to a rapid early-strength self-repairing shotcrete and a construction method thereof. Background Art
[0002] Shotcrete is widely used in deep foundation pit support, and its early strength and crack resistance directly affect the safety of the project. As the depth of the foundation pit increases, the deformation of the surrounding rock intensifies, and shotcrete is prone to cracks. At present, the following methods are mainly used at home and abroad to improve the performance of shotcrete: adding steel fiber or synthetic fiber to improve toughness; using high-efficiency water reducer to improve workability; using accelerator to improve early strength; optimizing construction technology to reduce cracks.
[0003] Through searching, we found similar patents: CN112174632A, CN114477871A, CN116621539A. Through analysis and comparison, we found that these three existing patents mainly innovate from different angles such as component design, functional modification and admixture optimization.
[0004] The innovative idea of patent CN112174632A is to use acoustic function as the main goal of shotcrete, use porous materials such as shell powder and diatomaceous earth as acoustic functional components, and achieve structural enhancement through the combination of composite fibers. It focuses on solving the noise control problem in tunnel engineering, while taking into account early strength and crack resistance.
[0005] Patent CN114477871B starts with material modification, innovatively uses nickel oxide / graphene to modify polyacrylonitrile fibers, and achieves fiber functionalization through a specific spinning process. This technology significantly improves the toughness and durability of shotcrete through the composite modification of nanomaterials and fibers.
[0006] Patent CN116621539A focuses on the optimization of the admixture system and proposes a compounding technology of components such as zinc oxide particles, calcined phyllite powder, triterpenoid saponins, and anhydrous calcium chloride. By controlling the capillary structure and hydration process, it achieves a synergistic improvement in anti-seepage performance and early strength.
[0007] Existing shotcrete has problems of low early strength and high risk of cracking. The 1d compressive strength is generally lower than 10Mpa. The 3d compressive strength is difficult to reach 20Mpa. The strength development speed is slow, which affects the construction progress.
[0008] Traditional self-repair technology cannot achieve rapid repair, and the strength generally decreases after repair.
[0009] Existing self-repairing microcapsules have poor environmental sensitivity and are prone to premature destruction.
[0010] Traditional technology cannot ensure the interface bonding strength between the repair material and the substrate. Traditional repair takes a long time: 7-14 days. Strength decreases after repair: 20-30%. Interface bonding strength is poor: ≤1.5.
[0011] Traditional construction technology is complex and quality control is difficult. Summary of the invention
[0012] In order to solve the above-mentioned problems existing in the prior art, the purpose of the present invention is to provide a rapid early-strength self-repairing shotcrete and a construction method thereof, and proposes a synergistic mechanism of double microcapsules and rapid early-strength systems. Through complex interface regulation and precise design of functional components, the simultaneous improvement of concrete self-repairing performance and early strength is achieved.
[0013] The technical solution adopted by the present invention is:
[0014] A rapid early strength self-repairing shotcrete, comprising a base layer, an interface layer and a functional layer arranged in sequence, wherein the functional layer comprises a rapid early strength system and a composite microcapsule system distributed in the rapid early strength system;
[0015] Among them, the composite microcapsule system includes inner layer microcapsules and outer layer microcapsules. The inner layer microcapsules include bisphenol A epoxy resin as the core material and modified fatty amine as the curing agent, and the outer layer microcapsules include modified polyurethane; the rapid early strength system includes a gelling material, an admixture system and a fiber component; the interface layer includes organic components such as acrylic emulsion and epoxy resin, and inorganic components such as nano-silicon dioxide and nano-alumina.
[0016] The double microcapsule system adopts a unique inner and outer layer structure design. The outer layer is a modified polyurethane shell constructed by the MDI / PTMG system, which is stress sensitive and environmentally stable, triggering rupture at a stress level of 1.5-2.0MPa; the inner layer contains bisphenol A epoxy resin and modified fatty amine curing agent, with an encapsulation rate of 85-95%. Through silanization surface treatment, chemical bonding with the cement matrix is achieved to ensure the stability and repair effect of the microcapsules.
[0017] The rapid early-strength cementitious material system achieves performance improvement through the synergistic effect of multiple components. It uses P.II52.5 silicate cement as the main component, combined with sulphoaluminate cement as the early-strength component, and supplemented with ternary mineral admixtures to regulate the hydration process. It innovatively adopts the solid and liquid accelerator compounding technology, combines the admixture system of high-efficiency water reducer and etherified starch toughening agent, and introduces the dual reinforcement mechanism of steel fiber and ultrafine polypropylene fiber.
[0018] The interface strengthening technology adopts an organic-inorganic composite reinforcement system, which provides interface toughness through the organic network of acrylic emulsion and epoxy resin, and the inorganic phase of nano-silica and alumina enhances the chemical bonding. The surface modification treatment of silane coupling agent ensures the interface stability between microcapsules and the matrix, and the interface transition zone with a treatment depth of 2 to 3 mm achieves stress gradient optimization.
[0019] The layered spraying process innovatively designs a three-layer structural system of base layer, interface layer and functional layer. The base layer provides structural support, the interface layer realizes transition connection, and the functional layer integrates early strength and self-repairing properties. The proportions and construction parameters of each layer are optimized to ensure the synergistic performance of the overall performance. The uniform dispersion of microcapsules, the full reaction of the interface layer and the strength development of the functional layer are effectively controlled.
[0020] As a preferred embodiment of the present invention, the rapid early strength system comprises the following components in parts by weight:
[0021] Cementitious materials: 75-80 parts of P.II52.5 silicate cement, 15-22 parts of mineral admixture combination, 5-8 parts of early strength component;
[0022] Admixture system: 0.8-1.2 parts of polycarboxylic acid high-efficiency water reducing agent, 3-5 parts of liquid accelerating agent, 0.3-0.5 parts of toughening agent, 0.02-0.03 parts of air entraining agent;
[0023] Fiber components: steel fiber 25-30kg / m3, polypropylene fiber 1-1.5kg / m3.
[0024] As a preferred embodiment of the present invention, the interface layer comprises the following components in parts by weight:
[0025] Organic components: 40-50 parts of acrylic emulsion, 10-15 parts of epoxy resin;
[0026] Inorganic components: 3-5 parts of nano silicon dioxide and 2-3 parts of nano aluminum oxide.
[0027] As a preferred embodiment of the present invention, the base layer includes the following components: 420-450 kg / m3 of cement, 750-800 kg / m3 of sand, 950-1000 kg / m3 of crushed stone, 0.40-0.45 kg / m3 of water-cement ratio, and 0.6-0.8% of fiber content.
[0028] A construction method for rapid early-strength self-repairing shotcrete comprises the following steps:
[0029] S1: prepare composite microcapsule system, rapid early strength system, interface layer material and base layer material respectively;
[0030] S2: Foundation treatment: level and clean the surface, and lay the steel mesh;
[0031] S3: spraying the base layer, interface layer and functional layer in sequence;
[0032] S4: Initial maintenance and later maintenance.
[0033] As a preferred embodiment of the present invention, in step S1, the preparation of the composite microcapsule system specifically includes the following steps:
[0034] S11: preparation of inner layer microcapsules;
[0035] S12: outer coating process;
[0036] S13: Surface modification treatment.
[0037] As a preferred solution of the present invention, step S11 specifically includes the following steps:
[0038] Dissolving the modified epoxy resin in toluene to prepare a 25-30 wt % solution;
[0039] Add 2-3% PVA-217 aqueous solution dropwise at 65-70°C;
[0040] Initial stirring speed is 800-1000 rpm, and after 30 minutes, it is reduced to 400-500 rpm;
[0041] After reacting for 4 to 5 hours, centrifugation, washing and drying are performed to obtain inner layer microcapsules with an encapsulation rate of 85% to 95%;
[0042] The curing time at 20°C is 6 to 12 hours, and the curing shrinkage is ≤0.5%.
[0043] As a preferred solution of the present invention, step S12 specifically includes the following steps:
[0044] The prepared inner layer microcapsules are dispersed in an aqueous solution of PTMG and TMP;
[0045] MDI is dissolved in dichloromethane to prepare 15-20wt% oil phase;
[0046] Add the oil phase dropwise into the water phase containing the inner layer microcapsules at 40-45°C and 600-800 rpm;
[0047] Add 0.8-1.2% emulsifier;
[0048] The reaction was continued for 3 to 4 hours, and the organic solvent was removed by distillation under reduced pressure;
[0049] Polyurethane is in situ polymerized on the surface of the inner microcapsules to form an outer shell.
[0050] As a preferred solution of the present invention, step S13 specifically includes the following steps:
[0051] The silanization was carried out by solution impregnation method;
[0052] Use γ-aminopropyltriethoxysilane, the dosage is 0.8-1.2%;
[0053] Immerse in a mixed solution of ethanol / water in a weight ratio of 9:1 for 2 hours;
[0054] Vacuum drying at 50-60°C for 4-6 hours;
[0055] After modification, the grafting rate is ≥95% and the suspension stability is >48 hours.
[0056] As a preferred embodiment of the present invention, in step S3:
[0057] Spraying environment requirements: temperature 20±2℃; humidity: ≥95%; wind speed: ≤3m / s; base surface temperature: 15-25℃;
[0058] Spraying equipment parameters: spraying pressure 0.6~0.8Mpa; wind pressure 0.5~0.7Mpa; delivery pipe diameter 50~65mm; nozzle diameter 25~35mm;
[0059] Spraying operation requirements: spraying distance 0.8~1.2m; spraying angle 75~90°; spraying speed 2~3m2 / min; single layer thickness 30~50mm.
[0060] The beneficial effects of the present invention are:
[0061] The present invention designs a stress-sensitive dual microcapsule structure to achieve intelligent identification and directional repair of cracks. The present invention develops a rapid early strength system comprising sulphoaluminate cement, mineral admixtures, etc., which significantly improves the early strength. The present invention ensures the effective bonding between the functional layers through layered spraying process and interface strengthening technology. From the application effect point of view, the present invention has achieved breakthrough indicators such as 1d compressive strength ≥ 15MPa, crack repair rate ≥ 90%, and interface bonding strength ≥ 2.5MPa, providing a new technical route for improving the performance of shotcrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 It is a schematic diagram of the layered injection structure of the present invention;
[0063] Figure 2 is a schematic diagram of the structure of the composite microcapsule system;
[0064] Figure 3 This is the schematic diagram of microcapsule repair;
[0065] Figure 4 is the interface enhancement mechanism diagram;
[0066] Figure 5 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION
[0067] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0068] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0069] 1. Innovative preparation process:
[0070] like Figure 1 As shown, a rapid early strength self-repairing shotcrete of the present invention comprises a base layer, an interface layer and a functional layer arranged in sequence, wherein the functional layer comprises a rapid early strength system and a composite microcapsule system distributed in the rapid early strength system;
[0071] Among them, the composite microcapsule system includes inner layer microcapsules and outer layer microcapsules. The inner layer microcapsules include bisphenol A epoxy resin as the core material and modified fatty amine as the curing agent, and the outer layer microcapsules include modified polyurethane; the rapid early strength system includes a gelling material, an admixture system and a fiber component; the interface layer includes organic components such as acrylic emulsion and epoxy resin, and inorganic components such as nano-silicon dioxide and nano-alumina.
[0072] (I) Design of composite microcapsule system:
[0073] 1. Outer microcapsule structure:
[0074] Shell material: modified polyurethane (MDI / PTMG system);
[0075] Shell thickness: 2-5 μm;
[0076] Particle size distribution: 50-100 μm;
[0077] Destruction stress: 1.5~2.0Mpa;
[0078] Thermal stability: ≤180℃;
[0079] Shelf life: ≥12 months.
[0080] 2. Inner microcapsule structure:
[0081] Core material: bisphenol A epoxy resin;
[0082] Curing agent: modified fatty amine;
[0083] Encapsulation rate: 85% to 95%;
[0084] Curing time: 6-12h (20°C);
[0085] Curing shrinkage: ≤0.5%;
[0086] 3. Microcapsule modification treatment:
[0087] Surface silanization treatment;
[0088] Coupling agent dosage: 0.8%~1.2%;
[0089] Grafting rate: ≥95%;
[0090] Dispersion stability: Excellent.
[0091] 4. The mechanism of action of self-repairing shotcrete:
[0092] Figure 2 is a schematic diagram of the structure of the composite microcapsule system; Figure 3 This is the schematic diagram of microcapsule repair.
[0093] In the initial stage, the double composite microcapsules are stably dispersed in the cement matrix. The microcapsules adopt a double-layer structure design: the inner layer is a bisphenol A epoxy resin (E-51) and a modified fatty amine curing agent system with a high encapsulation rate of 85% to 95%; the outer layer is a modified polyurethane shell layer constructed by the MDI / PTMG system, with a shell thickness of 2 to 5 μm, and has good interface compatibility with the matrix after silanization treatment.
[0094] When cracks appear in the concrete structure, stress concentration causes the local stress level to reach 1.5-2.0 MPa, triggering the rupture of the outer polyurethane shell. Subsequently, the inner microcapsules release epoxy resin repair agent and modified fatty amine curing agent. Under the action of capillary suction, the repair components quickly diffuse and migrate to the cracks.
[0095] The repair material undergoes a cross-linking and curing reaction in the crack area. The introduction of polyether-type amino-terminated butadiene acrylonitrile copolymer provides a toughening effect, and the addition of nano-silica (particle size 20-30nm) improves the rheological properties of the system. The interface layer modified by KH-550 coupling agent promotes the chemical bonding between the repair material and the matrix, and the interface bonding strength reaches more than 2.5MPa.
[0096] At 20±2℃, the repair reaction is completed within 6 to 12 hours, and the curing shrinkage is controlled within 0.5%. The compressive strength recovery rate of the repaired area is ≥90%, and the dense structure formed has excellent penetration resistance, and the chloride ion diffusion coefficient is ≤2.0×10 -12 m 2 / s.
[0097] This self-repair mechanism realizes intelligent damage repair of concrete structures through stress-induced double microcapsule rupture, directional migration of repair materials and interfacial chemical reaction, significantly improving the durability and service life of engineering structures.
[0098] (II) Preparation process of composite microcapsule system:
[0099] 1. Preparation of inner layer microcapsules:
[0100] Core material: bisphenol A epoxy resin (E-51): molecular weight 700-900, epoxy value 0.48-0.54 mol / 100g; adding 5%-8% reactive toughening agent (polyether type amino-terminated butadiene acrylonitrile copolymer); adding 2%-3% nano-silicon dioxide (20-30nm) to improve fluidity.
[0101] Curing agent: modified fatty amine: obtained by partially modifying diethylenetriamine (DETA) through epoxy resin; the amine value is controlled at 400-450 mgKOH / g.
[0102] Preparation process:
[0103] Dissolving the modified epoxy resin in toluene to prepare a 25-30 wt % solution;
[0104] Add 2% to 3% PVA-217 aqueous solution dropwise at 65 to 70°C;
[0105] Initial stirring speed is 800-1000 rpm, and after 30 minutes, it is reduced to 400-500 rpm;
[0106] After 4 to 5 hours of reaction, centrifuge, wash and dry;
[0107] Obtaining inner layer microcapsules with an encapsulation rate of 85-95%;
[0108] The curing time at 20°C is 6 to 12 hours, and the curing shrinkage is ≤0.5%.
[0109] 2. Outer coating process:
[0110] Shell material preparation:
[0111] MDI and PTMG (molecular weight 2000) are the main ingredients;
[0112] Add 3% to 5% TMP as a cross-linking agent;
[0113] NCO / OH molar ratio 1.05-1.15;
[0114] Add 2% to 3% of silicone modifier (KH-560) to improve interfacial compatibility;
[0115] Add 1% to 2% antioxidant (1076) and 0.5% to 1% ultraviolet absorber (UV-531).
[0116] Coating process:
[0117] Dispersing the prepared inner layer microcapsules in an aqueous solution of PTMG and TMP (pH 8.0-8.5);
[0118] MDI is dissolved in dichloromethane to prepare 15-20wt% oil phase;
[0119] Add the oil phase dropwise into the water phase containing the inner layer microcapsules at 40-45°C and 600-800 rpm;
[0120] Add 0.8% to 1.2% emulsifier (Span-80 / Tween-80 mixture, HLB value 7-9);
[0121] The reaction was continued for 3 to 4 hours, and the organic solvent was removed by distillation under reduced pressure;
[0122] Polyurethane is in situ polymerized on the surface of the inner microcapsules to form an outer shell.
[0123] 3. Surface modification:
[0124] The silanization was carried out by solution impregnation method;
[0125] Use γ-aminopropyltriethoxysilane (KH-550) at a dosage of 0.8% to 1.2%;
[0126] Immerse in a mixed solution of ethanol / water (9:1) for 2 h;
[0127] Vacuum drying at 50-60°C for 4-6 hours;
[0128] After modification, the grafting rate is ≥95% and the suspension stability is >48 hours.
[0129] The shell thickness of the final product is 2-5 μm, the particle size is 50-100 μm, the breaking stress is 1.5-2.0 MPa, and the storage period is ≥12 months.
[0130] (III) Formula of rapid early strength system:
[0131] 1. Composition of cementitious materials (weight ratio):
[0132] P.II52.5 Portland cement: 75-80%;
[0133] Mineral admixture combination: silica fume 5% to 8%; granulated slag 8% to 10%; fly ash 2% to 4%;
[0134] Early strength components: sulphoaluminate cement: 3%~5%; accelerator: 2%~3%.
[0135] 2. Admixture system:
[0136] Polycarboxylic acid high-efficiency water reducer: 0.8%~1.2%;
[0137] Liquid accelerating agent: 3% to 5% (solid content 50%);
[0138] Toughening agent (etherified starch): 0.3% to 0.5%;
[0139] Air entraining agent: 0.02%~0.03%.
[0140] 3. Fiber components:
[0141] Steel fiber: 25~30kg / m 3 (Concrete): length 25mm; diameter 0.3mm; tensile strength ≥1200Mpa;
[0142] Polypropylene fiber: 1~1.5kg / m 3 (Concrete): Length 12 mm; Diameter 18 μm.
[0143] 4. Early strength system mechanism:
[0144] The rapid early strength system and the composite microcapsule self-repairing system form a synergistic effect through interface interaction and microstructure regulation. The rapid hydration products of sulphoaluminate cement and the CSH gel of silicate cement jointly build early strength and provide a stable environment for the microcapsules. The surface of the silanized composite microcapsules forms a chemical bond with the cement hydration products, and the γ-aminopropyltriethoxysilane on its surface undergoes a condensation reaction with the CSH gel to ensure the interface stability of the microcapsules.
[0145] The polycarboxylate water reducer disperses cement particles and microcapsules simultaneously through electrostatic repulsion, preventing the microcapsules from agglomerating in the matrix. The network structure formed by the etherified starch toughening agent is compatible with the modified polyurethane shell layer on the outer layer of the microcapsules, improving the stress sensitivity of the microcapsules. The microbubble system generated by the air entraining agent provides a channel for the migration of repair materials after the microcapsules are ruptured.
[0146] The multi-scale reinforcement system constructed by steel fiber and polypropylene fiber controls the crack width within 0.3mm through stress redistribution, which matches the repair range of microcapsules. The bridging effect of the fiber can also slow down the crack expansion rate, providing time for the full reaction of the repair material. The volcanic ash reaction of silica fume and granulated slag continuously optimizes the pore structure, which not only creates conditions for the penetration and migration of the repair material, but also forms chemical bonds with the repair material to improve the bonding strength of the repair area.
[0147] The synergistic mechanism of the early-strength system and the self-repairing system realizes the unification of interface structure regulation and stress response at the microscale, ensures the effective performance of rapid early-strength and intelligent repair functions, and provides performance guarantee for engineering structures throughout their life cycle.
[0148] (IV) Interface strengthening technology:
[0149] 1. Surface modification:
[0150] Silane coupling agent: KH550;
[0151] Dosage: 200~300g / m 2 ;
[0152] pH value: 5.5-6.5;
[0153] Grafting rate: ≥95%.
[0154] 2. Interface enhancer composition:
[0155] Organic components: acrylic emulsion 40% to 50%; epoxy resin 10% to 15%;
[0156] Inorganic components: nano silicon dioxide 3% to 5%; nano aluminum oxide 2% to 3%.
[0157] 3. Interface treatment process:
[0158] Surface treatment depth: 2-3mm;
[0159] Curing time: 2 to 4 hours;
[0160] Bonding strength: ≥2.5Mpa.
[0161] 4. Interface layer mechanism:
[0162] like Figure 4As shown in the figure, the interface layer constructs a synergistic mechanism of the rapid early strength system and the microcapsule self-healing system through chemical bonding and physical action. The organic network formed by the acrylic emulsion in the interface enhancer and the epoxy resin enhances the bonding force between the CSH gel and the composite microcapsules in the early strength system through interface wetting. The inorganic phase formed by nano-silica and nano-alumina in the interface layer not only reacts chemically with the cement hydration products, but also forms covalent bonds with the silane groups on the surface of the microcapsules.
[0163] The organic components of the interface enhancer provide interface toughness through the physical entanglement of molecular segments, synergize the reinforcement effect of steel fibers and polypropylene fibers, and alleviate the premature damage of microcapsules caused by stress concentration. At the same time, the nanoscale pore network formed in the interface layer provides a channel for the directional migration of repair materials, improving the repair efficiency. The grafting effect of silane coupling agent KH550 on the interface layer allows the surface of the microcapsules to form a chemical bond with the cement matrix, improving the stress sensitivity of the microcapsules and the repair triggering accuracy.
[0164] The depth of the modified interface layer is controlled at 2-3mm, ensuring the stress gradient distribution in the interface transition area and avoiding the stress mismatch between the early strength system and the self-repairing system. After 2-4 hours of interface curing, the formed bonding strength exceeds 2.5MPa, which provides a guarantee for the stable presence of microcapsules and the interface reaction of the repair material. This interface synergy mechanism realizes the effective connection between early strength development and self-repairing function, and improves the durability of the overall structure.
[0165] (V) Layered injection structure design:
[0166] 1. Base layer ratio (kg / m 3 ):
[0167] Cement 420-450, sand 750-800, crushed stone (5-10mm) 950-1000, water-cement ratio 0.40-0.45, fiber content 0.6%-0.8%.
[0168] 2. Interface layer structure:
[0169] Thickness: 2~3mm.
[0170] Dosage of reinforcing agent: 0.2~0.3kg / m 2 .
[0171] Curing time: 2 to 4 hours.
[0172] Compressive strength: ≥45Mpa.
[0173] 3. Functional layer ratio (kg / m 3): Cement 450~480, sand 720~750, crushed stone 900~950, microcapsule 15~20, water-cement ratio 0.38~0.42.
[0174] 4. Principle of layered injection structure
[0175] like Figure 1 As shown in the figure, the base layer is used as the supporting structure, with a conventional mix ratio (cement 420-450 kg / m 3 , sand 750~800kg / m 3 , crushed stone 950~1000kg / m 3 ), the water-binder ratio is controlled at 0.40-0.45, and the fiber content is 0.6% to 0.8%. This ratio design not only ensures the working performance of the base layer, but also provides a stable matrix support for the rapid early strength system. The fiber components in the base layer and the double fibers in the early strength system work together to form a continuous stress transfer network.
[0176] The interface layer is the key transition area between the base layer and the functional layer, and its thickness is controlled at 2-3 mm. The interface layer is reinforced with a reinforcing agent (0.2-0.3 kg / m 2 ) to organically combine the early strength components of the base layer with the self-repairing system of the functional layer. The composite modification of acrylic emulsion and epoxy resin provides interfacial bonding, while nano-silica and nano-alumina enhance interfacial strength through chemical bonding. The curing time of 2 to 4 hours ensures that the interfacial layer reaches a compressive strength of more than 45MPa, providing a solid foundation for the construction of subsequent functional layers.
[0177] The functional layer is essentially a combination of a rapid early strength system and a composite microcapsule self-repairing system. Its proportion adopts a complete early strength system formula: P.II 52.5 silicate cement (75% to 80%), silica fume (5% to 8%), granulated slag (8% to 10%), fly ash (2% to 4%) as the basic cementitious material, combined with sulphoaluminate cement (3% to 5%) and accelerator (2% to 3%) as early strength components, and uses polycarboxylic acid high-efficiency water reducer (0.8% to 1.2%), liquid accelerator (3% to 5%), etherified starch (0.3% to 0.5%) and air entraining agent (0.02% to 0.03%) as an admixture system, as well as steel fiber (25 to 30 kg / m 3 ) and polypropylene fiber (1~1.5kg / m 3 ) as a reinforcing component. At the same time, 15-20 kg / m 3 The double composite microcapsules give it self-repairing function.
[0178] 2. Construction process parameters:
[0179] (I) Grassroots processing:
[0180] 1. Surface treatment requirements
[0181] Surface flatness deviation: ≤5mm;
[0182] Moisture content: 6% to 8%;
[0183] Cleanliness: No dust or oil.
[0184] 2. Steel mesh layout:
[0185] Grid size: 150×150mm;
[0186] Steel bar diameter: 6-8mm;
[0187] Protective layer thickness: 15~20mm.
[0188] (II) Spraying process parameters:
[0189] Figure 5 It is a flow chart of the preparation method of the present invention.
[0190] 1. Environmental requirements:
[0191] Temperature: 20±2℃;
[0192] Humidity: ≥95%;
[0193] Wind speed: ≤3m / s;
[0194] Base surface temperature: 15~25℃.
[0195] 2. Injection equipment parameters:
[0196] Spray pressure: 0.6~0.8Mpa; wind pressure: 0.5~0.7Mpa; delivery pipe diameter: 50~65mm; nozzle diameter: 25~35mm.
[0197] 3. Spraying operation requirements:
[0198] Spray distance: 0.8~1.2m; spray angle: 75~90°;
[0199] Spray speed: 2~3m 2 / min; single layer thickness: 30~50mm.
[0200] (III) Maintenance system:
[0201] 1. Initial curing (0-24h): temperature: 20±2℃;
[0202] Relative humidity: ≥95%;
[0203] Maintenance method: spray maintenance;
[0204] Frequency: 2h / time.
[0205] 2. Late maintenance (1-7 days): temperature: 20±2℃;
[0206] Relative humidity: ≥90%;
[0207] Maintenance method: mulching and watering;
[0208] Frequency: 2 times / d.
[0209] 3. Technical indicators:
[0210] (I) Mechanical properties:
[0211] 1. Compressive strength:
[0212] 1d: ≥15Mpa;
[0213] 3d: ≥25Mpa;
[0214] 28d:≥45Mpa.
[0215] 2. Bending strength:
[0216] 1d: ≥2.5Mpa;
[0217] 3d: ≥4.0Mpa;
[0218] 28d: ≥6.5Mpa.
[0219] 3. Bond strength:
[0220] 3d: ≥1.0Mpa;
[0221] 28d: ≥1.5Mpa.
[0222] (II) Self-repair performance:
[0223] 1. Crack repair capability:
[0224] Repairable crack width: ≤0.3mm; repair time: 12~24h;
[0225] Repair depth: ≥20mm;
[0226] Strength recovery rate: ≥90%.
[0227] 2. Durability index:
[0228] Impermeability grade: P12;
[0229] Antifreeze grade: F300;
[0230] Anti-carbonization performance: excellent;
[0231] Chloride ion diffusion coefficient: ≤2.0×10 -12 m 2 / s.
[0232] 4. Embodiment:
[0233] Deep foundation pit support engineering design: foundation pit depth 15 ~ 30m, support thickness 100 ~ 150mm, environment above groundwater level. The base layer ratio uses cement 430kg / m 3 、Sand 780kg / m 3 、Crushed stone 980kg / m 3 The water-binder ratio is 0.42, and the steel fiber is added in 0.7%. The interface layer adopts the organic component ratio of 45% acrylic emulsion and 12% epoxy resin, the inorganic component ratio of 4% nano silicon dioxide and 2.5% nano aluminum oxide, and the reinforcing agent dosage is 0.25kg / m 2 The amount of P.II 52.5 cement in the functional layer mix is increased to 470kg / m 3 , the proportion of sulphoaluminate cement increased to 4.5%, the amount of accelerator was 2.8%, and the amount of composite microcapsules added was 18kg / m 3 , the water-cement ratio is reduced to 0.40. The wet spraying process is used during construction, the spraying pressure is controlled at 0.7MPa, the wind pressure is 0.6MPa, the spraying distance is 1.0m, the single-layer spraying thickness is 40mm, and layered continuous spraying is used.
[0234] Tunnel lining engineering design: initial support 150-200mm, secondary lining 250-300mm. Increase the amount of cementitious materials used in the base layer to 440kg / m 3 , increase the steel fiber content to 0.75% to improve impact resistance. The amount of interface layer reinforcement agent is increased to 0.28kg / m 2 , prolonging the curing time to 3.5 hours. In the functional layer mix, the proportion of granulated slag is increased to 9.5%, the amount of liquid accelerating agent is increased to 4.5%, and the amount of composite microcapsules is increased to 20kg / m 3 At the same time, the amount of polypropylene fiber was increased to 1.4kg / m 3 , improve crack resistance. The construction adopts high-pressure wet spraying technology, the spraying pressure is increased to 0.8MPa, pulse spraying is adopted, the single layer thickness is controlled at 45mm, and the interval between layers is 2 hours.
[0235] Underground structure maintenance plan: for crack repair, leakage treatment and structural reinforcement. Reduce the amount of crushed stone in the base layer to 920kg / m 3 , increase the mortar ratio. The interface layer uses highly permeable silicone modified epoxy resin, and the amount of reinforcing agent is 0.3kg / m 2 The functional layer increases the proportion of silica fume to 7.5%, increases the amount of etherified starch to 0.45%, and controls the amount of composite microcapsules at 16kg / m3 , to ensure that the repair material fully penetrates. Use low-pressure multiple injection technology, reduce the injection pressure to 0.6MPa, control the single layer thickness at 35mm, and strengthen maintenance measures.
[0236] Layered spraying technology is used in all application scenarios. The interface layer is treated immediately after the base layer is sprayed, and the functional layer is sprayed after the interface layer reaches the strength requirements. The maintenance system is strictly implemented. The temperature is maintained at 20±2℃ and the relative humidity is ≥95% within 24 hours of initial maintenance, and spraying is performed once every 2 hours; the temperature is maintained at 20±2℃ and the relative humidity is ≥90% within 7 days of later maintenance, and watering is performed twice a day. By adjusting the mix ratio and construction process parameters, the early strength and self-healing performance of shotcrete in each application scenario are ensured to meet the engineering requirements.
[0237] Table 1 shows the effects of using this technology in different application scenarios.
[0238]
[0239]
[0240] The present invention is not limited to the above-mentioned optional implementation modes. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that fall within the scope defined by the claims of the present invention fall within the protection scope of the present invention.
Claims
1. A rapid early strength self-repairing shotcrete, characterized in that: It includes a base layer, an interface layer and a functional layer arranged in sequence, wherein the functional layer includes a rapid early strength system and a composite microcapsule system distributed in the rapid early strength system; Among them, the composite microcapsule system includes inner layer microcapsules and outer layer microcapsules. The inner layer microcapsules include bisphenol A epoxy resin as the core material and modified fatty amine as the curing agent, and the outer layer microcapsules include modified polyurethane; the rapid early strength system includes a gelling material, an admixture system and a fiber component; the interface layer includes organic components such as acrylic emulsion and epoxy resin, and inorganic components such as nano-silicon dioxide and nano-alumina.
2. The rapid early strength self-repairing shotcrete according to claim 1, characterized in that: The rapid early strength system comprises the following components in parts by weight: Cementitious materials: 75-80 parts of P.II52.5 silicate cement, 15-22 parts of mineral admixture combination, 5-8 parts of early strength component; Admixture system: 0.8-1.2 parts of polycarboxylic acid high-efficiency water reducing agent, 3-5 parts of liquid accelerating agent, 0.3-0.5 parts of toughening agent, 0.02-0.03 parts of air entraining agent; Fiber composition: steel fiber 25-30kg / m 3 , Polypropylene fiber 1~1.5kg / m 3 .
3. The rapid early strength self-repairing shotcrete according to claim 1, characterized in that: The interface layer comprises the following components in parts by weight: Organic components: 40-50 parts of acrylic emulsion, 10-15 parts of epoxy resin; Inorganic components: 3-5 parts of nano silicon dioxide and 2-3 parts of nano aluminum oxide.
4. The rapid early strength self-repairing shotcrete according to claim 1, characterized in that: The base layer includes the following components: cement 420-450 kg / m 3 , sand 750~800kg / m 3 , Crushed stone 950~1000kg / m 3 , water-cement ratio 0.40~0.45kg / m 3 , fiber content 0.6~0.8%.
5. A construction method of rapid early strength self-repairing shotcrete, used for constructing the rapid early strength self-repairing shotcrete according to claim 1, characterized in that: The following steps are involved: S1: prepare composite microcapsule system, rapid early strength system, interface layer material and base layer material respectively; S2: Foundation treatment: smooth and clean the surface, and lay the steel mesh; S3: spraying the base layer, interface layer and functional layer in sequence; S4: Initial maintenance and later maintenance.
6. The construction method of a rapid early-strength self-repairing shotcrete according to claim 5, characterized in that: In step S1, the preparation of the composite microcapsule system specifically includes the following steps: S11: preparation of inner layer microcapsules; S12: outer coating process; S13: Surface modification treatment.
7. The construction method of a rapid early-strength self-repairing shotcrete according to claim 6, characterized in that: Step S11 specifically includes the following steps: Dissolving the modified epoxy resin in toluene to prepare a 25-30 wt % solution; Add 2-3% PVA-217 aqueous solution dropwise at 65-70°C; Initial stirring speed is 800-1000 rpm, and after 30 minutes, it is reduced to 400-500 rpm; After reacting for 4 to 5 hours, centrifugation, washing and drying are performed to obtain inner layer microcapsules with an encapsulation rate of 85% to 95%; The curing time at 20°C is 6 to 12 hours, and the curing shrinkage is ≤0.5%.
8. The construction method of the rapid early-strength self-repairing shotcrete according to claim 6 is characterized by: Step S12 specifically includes the following steps: The prepared inner layer microcapsules are dispersed in an aqueous solution of PTMG and TMP; MDI is dissolved in dichloromethane to prepare 15-20wt% oil phase; Add the oil phase dropwise into the water phase containing the inner layer microcapsules at 40-45°C and 600-800 rpm; Add 0.8-1.2% emulsifier; The reaction was continued for 3 to 4 hours, and the organic solvent was removed by distillation under reduced pressure; Polyurethane is in situ polymerized on the surface of the inner microcapsules to form an outer shell.
9. The construction method of a rapid early-strength self-repairing shotcrete according to claim 6, characterized in that: Step S13 specifically includes the following steps: Silanization was carried out by solution impregnation method; Use γ-aminopropyltriethoxysilane, the dosage is 0.8-1.2%; Immerse in a mixed solution of ethanol / water in a weight ratio of 9:1 for 2 hours; Vacuum drying at 50-60°C for 4-6 hours; After modification, the grafting rate is ≥95% and the suspension stability is >48 hours.
10. The construction method of the rapid early-strength self-repairing shotcrete according to claim 5, characterized in that: In step S3: Spraying environment requirements: temperature 20±2℃; Humidity: ≥95%; Wind speed: ≤3m / s; base surface temperature: 15-25℃; Spraying equipment parameters: spraying pressure 0.6~0.8Mpa; wind pressure 0.5~0.7Mpa; delivery pipe diameter 50~65mm; nozzle diameter 25~35mm; Spraying operation requirements: spraying distance 0.8~1.2m; spraying angle 75~90°; spraying speed 2~3m 2 / min; single layer thickness 30~50mm.
Citation Information
Patent Citations
Sprayed concrete and preparation method thereof
CN112174632A
Ultrahigh-toughness alkali-activated shotcrete and preparation method thereof
CN114477871A
High-viscosity high-impermeability fine stone sprayed concrete and preparation method thereof
CN116621539A
Cited By
Centrifugal casting corrosion-resistant concrete pipeline and preparation method thereof
CN120349129A